Appropriate financial instruments for public-private partnership to boost cross-border infrastructural development-EU experience - Willem van der Geest; Jorge Nunez-Ferrer (Asian Development Bank Institute (ADBI), 2011)
The member states of the European Union (EU) and the EU institutions have increasingly been using public-private partnerships (PPPs) to accelerate the development of (ambitious) trans-national infrastructure. This paper argues that in the EU (i) private sector partners remain risk-averse; and (ii) risk-pooling across a larger number of tax-payers tends to reduce the cost of risk to zero, making EU funds highly desirable and sought after for public infrastructure development. This paper argues that private equity has not been forthcoming to the extent that had been expected by those propagating this method of finance. In those instances where private non-publicly guaranteed resources have been used, the distribution of risks between public and private partners remained asymmetric, with public governmental bodies carrying the financial risks, which ultimately may become a contingent liability for the country's public finances. However, EU and European Investment Bank (EIB) public funding is used not simply because the risks are spread more widely, but rather because EU rules and regulations for using such funds lead to better preparation of projects and greater efficiency gains in project implementation and delivery.
Keywords: G32; H44; O19; 330; Public-Private Partnership; Private Equity; Verkehrsinvestition; Grenzüberschreitender Verkehr; EU-Staaten